1993
DOI: 10.1007/bf00014933
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of an acyl carrier protein gene promoter in vegetative and reproductive tissues

Abstract: The expression of an Arabidopsis acyl carrier protein (ACP) gene promoter has been examined in transgenic tobacco plants by linking it to the reporter gene beta-glucuronidase (GUS). Fluorometric analysis showed that the ACP gene promoter was most active in developing seeds. Expression was also high in roots, but significantly lower in young leaves and downregulated upon their maturation. Etiolated and light-grown seedlings showed the same level of GUS activity, indicating that this promoter is not tightly regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
3

Year Published

1994
1994
2004
2004

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
3
8
0
3
Order By: Relevance
“…Overall, these studies indicated that leaves and roots require different domains of the Acll.2 gene promoter for maximal expression. Deletion of the -520 to -321 region did not significantly alter Acl 1.2 promoter activity in developing leaves (P<0.5), which was comparable to median activity levels observed in transformant populations containing the -840 to + 74 promoter region found previously [2]. In contrast, removal of the -320 to -236 region resulted in a significant decrease in GUS activity, with median levels observed in A5 transformants about 9-fold lower than those observed in A4-transformed plants.…”
Section: ' Deletion Analysis Of the Acyl Carrier Protein Acll2 Genesupporting
confidence: 66%
See 3 more Smart Citations
“…Overall, these studies indicated that leaves and roots require different domains of the Acll.2 gene promoter for maximal expression. Deletion of the -520 to -321 region did not significantly alter Acl 1.2 promoter activity in developing leaves (P<0.5), which was comparable to median activity levels observed in transformant populations containing the -840 to + 74 promoter region found previously [2]. In contrast, removal of the -320 to -236 region resulted in a significant decrease in GUS activity, with median levels observed in A5 transformants about 9-fold lower than those observed in A4-transformed plants.…”
Section: ' Deletion Analysis Of the Acyl Carrier Protein Acll2 Genesupporting
confidence: 66%
“…Previously we showed that Acll.2 gene promoter activity declines approximately 16-fold during leaf maturation in transformed tobacco plants [2]. Interestingly, deletion of the -320 to -236 region resulted in GUS activity levels in young leaves that were nearly the same as those observed in mature leaves containing the fulllength Acll.2 GUS construct (shown for comparison in Fig.…”
Section: ' Deletion Analysis Of the Acyl Carrier Protein Acll2 Genementioning
confidence: 80%
See 2 more Smart Citations
“…The segregation (18,28) and chimerism (2,3,4) in the dihaploid lines reveal only part of the reasons for this situatuion. On the other hand, we achieved considerable results with non-segregating DH (8,10,33 (11,12,44,123) etc. To explain the depression of the agronomic performance of the dihaploid lines several hypothesis were raised: -inbreeding depression and residual heterozygosity which seem similar to the phetype suppression after long-term self-fertilization in many cultivated species (5,17,18,19,20,23,114,115,116,117); -cytoplasmic and/or nuclear genes modifications (17,28,51), gross chromosomal changes ( 4 2, 117) or organ ells replication (113) as a result of the in vitro culture; -DNA amplification in comparison to the source genotype (29,30,114 the yield loss recovery could be achieved after several recurrent full-sib selections (148).…”
Section: Introductionmentioning
confidence: 94%